PENGARUH KOMPRES ALOE VERA TERHADAP FLEBITIS AKIBAT PEMASANGAN INFUS (IV LINE) - Friska Ernita Sitorus; Elok Lidiya Wati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Phlebitis can cause thrombus and embolism which can cause permanent damage to the vein and can cause infection if not treated properly. The aim of the study was to determine the effect of giving Aloe Vera gel on the scale of phlebitis. The study design used one group pretest-posttest. The variables in this study are Aloe Vera compresses as independent variables and phlebitis as the dependent variable. The population in this study were all patients who experienced phlebitis at Sembiring General Hospital in 2019. Sampling using Consecutive sampling techniques as many as 31 respondents. Data were collected by observation sheet of phlebitis scale and tested with Wilcoxon statistical test. The results showed that there was a change in the scale of phlebitis experienced by respondents who experienced changes from respondents who had not previously found that there were no symptoms of phlebitis after being given aloe vera compresses. Wilcoxon statistical test result show data Ï-value  0.000 < Î± 0.05 then Ho is rejected and Ha is accepted, which means that there is a significant effect between aloe vera compresses to changes in the degree of phlebitis. Any changes that occur in patients who have experienced phlebitis indicate that giving aloe vera compresses can indicate the results of changes that are quite effective. It is expected that health workers can apply non-pharmacological therapies such as aloe vera compresses for the treatment of phlebitis so that the services provided can be of higher quality and the services performed more precisely.